Roll-Stabilized Fully Actuated Control of Guided Projectiles with Practical Actuator Constraints - Binyuan, Wang; Junfang, Fan; Fangyi, Quan (2025 4th Conference on Fully Actuated System Theory and Applications (FASTA), 2025)
Aiming at the challenges of strong nonlinearity, significant parameter uncertainties, and susceptibility to external disturbances in the roll channel dynamics of guided projectiles, this paper proposes a roll-stabilized fully actuated control scheme incorporating practical actuator constraints based on Fully Actuated System (FAS) theory. A refined roll channel control model is established considering actuator failure modes and dynamic characteristics under realistic operational constraints, where system uncertainties and disturbances are aggregated as bounded external perturbations. A composite control architecture integrating feedback linearization and disturbance compensation is developed, comprising a baseline feedback controller and an adaptive compensation module. Numerical simulations demonstrate robust angular velocity tracking performance under scenarios involving actuator failures, bandwidth limitations, deflection saturation, and bounded external disturbances. The results validate the effectiveness and robustness of the proposed fully actuated controller in stabilizing guided projectiles under stringent operational conditions.